Vulnerability due to fluvial erosion: case of the Palo de Agua township, Municipality of Lorica, Department of Córdoba, Colombia. - Villadiego-Lorduy, Jorge (2021)
The present study assesses the vulnerability of the populated center in the township of Palo de Agua, located on the banks of the Sinú River, belonging to the municipality of Santa Cruz de Lorica, Department of Córdoba, Colombia.  A mixed approach methodology is followed, with interview techniques applied to key actors and also by means of quantitative calculations to evaluate total, physical, environmental, economic and social vulnerabilities, based on field recognition data and fluvial erosion processes data analysis gathered from critical geographical points; without omitting to consider hazards and risk estimation applicable to Pablo de Agua township.  It is inferred that the average total vulnerability constitutes the predominant vulnerability category at 84% level.